Pionieri in paradiso - Simonetta Grilli; Fabio Mugnaini (EtnoAntropologia)
The essay reflects on the processes of redefining the forms of living in a rural community, Trequanda (in the province of Siena), which has experienced a partial repopulation since the 1970s with the arrival of individuals (couples and families of various ages) from diverse socio-cultural and geographical backgrounds. They largely embody the values of the so-called «neo-ruralism» and share a desire to experience the area not as tourists but as genuine inhabitants: they engage with local social networks, participate in political and economic life in various ways, and move towards sharing and negotiating their presence and experiences with the locals. The stories of these «protogentrifiers » in many ways anticipate the arrival of an elite group (comprising prominent figures from politics, culture, entertainment, and finance) who, starting in the late 1990s, will invest significant funds to purchase and renovate farmhouses, transforming them into aesthetically valuable house that represent high social status, thus leading to a radical process of gentrification in the area.